Malignant Rhabdoid Tumor of the Lung in the Young Adult: A Case Report - Adel Attia; Moosa Suleman; Hesham Mosleh (Case Reports in Pulmonology)
Malignant rhabdoid tumor (MRT) is one of the most aggressive and lethal malignancies in pediatric oncology. Malignant rhabdoid tumor was initially described in 1978 as a rhabdomyosarcomatoid variant of a Wilms tumor because of its occurrence in the kidney and because of the resemblance of its cells to rhabdomyoblasts. The absence of muscular differentiation led Haas and colleagues to coin the term rhabdoid tumor of the kidney in 1981, Haas et al..